2000
DOI: 10.1103/physrevb.61.16736
|View full text |Cite
|
Sign up to set email alerts
|

Metal-induced gap states and Schottky barrier heights at nonreactive GaN/noble-metal interfaces

Abstract: We present ab-initio local density FLAPW calculations on non-reactive Nterminated [001] ordered GaN/Ag and GaN/Au interfaces and compare the results (such as metal induced gap states and Schottky barrier heights) with those obtained for GaN/Al, in order to understand the dependence of the relevant electronic properties on the deposited metal. Our results show that the density of gap states is appreciable only in the first semiconductor layer close to the interface. The decay length of the gap states in the sem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 23 publications
(19 reference statements)
2
35
0
Order By: Relevance
“…The corresponding p-type SBHs are shown in Table 1. Taking into account that our calculations are performed with soft pseudopotentials, our results are reasonably close to theoretical values, obtained with FLAPW calculations [9].…”
Section: Schottky Barrierssupporting
confidence: 89%
See 2 more Smart Citations
“…The corresponding p-type SBHs are shown in Table 1. Taking into account that our calculations are performed with soft pseudopotentials, our results are reasonably close to theoretical values, obtained with FLAPW calculations [9].…”
Section: Schottky Barrierssupporting
confidence: 89%
“…SBH (This work) SBH (from [9]) Au/GaN(001) 0.82 eV 1.08 eV Cu/GaN(001) 1.00 eV Al/GaN(001) 1.68 eV 1.51 eV The differences in the resulting Schottky barrier heights to those of [9] can be attributed to two reasons: the different treatment of core electrons (pseudopotentials versus all-electron potentials) and the neglect of spin-related phenomena in our calculations. These effects are expected to be more important for heavier atoms like Au than for lighter ones like Al: while the epitaxial geometry for the Al/GaN(001) used in this work is identical to that of [9], the equilibrium interfacial distance differ for Au/GaN (d 0 =1.40Å[this work] versus d 0 =1.34Å [9].…”
Section: Contactmentioning
confidence: 96%
See 1 more Smart Citation
“…The type of silicide interfaces, e.g., 8-fold or 6-fold, described above is a subtle example of this termination issue. For every compound semiconductor studied by numerical calculations, termination at polar interfaces has been a prominent parameter that leads to different SBHs, e.g., for GaAs(100), 39 GaN(100), 101 and ZnSe (100) 87 interfaces. General considerations would suggest that, everything else being equal, the anion-terminated interface should have a smaller n-type SBH than the one terminated on cations.…”
Section: Epitaxial Ms Interfaces and Theoretical Calculationsmentioning
confidence: 99%
“…Surface alloying can occur [14] and a large range of experimentally measured Schottky barrier heights has been reported (0.76-1.40 eV) at the Au to n-type GaN interface [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], using photoemission spectroscopy (PES), current-voltage (I-V) and capacitance voltage (C-V) characteristics, and internal photoemission [30]. However, the generally accepted value is about 1.08 eV [31]. Kurtin et al [32] suggested that the Schottky barrier height on GaN should depend directly on the work function or electronegativity difference between the metal electrode and GaN.…”
Section: Introductionmentioning
confidence: 99%